(untitled) (Alimentos Ciencia e Ingeniería, 2023)
Food drying is a practice that has brought several benefits to the food industry, facilitating transportation, increasing shelf life, and avoiding the need for special treatments or storage according to the product. Due to the benefits and great development in the field of drying in recent years, a review of the main drying techniques of Sechium edule (or chayote) has been developed. Bad practices, food waste, and poor nutrition are some of the problems that open up opportunities to work with the final producer to take advantage of food and extend its shelf life, especially foods with high humidity. In this sense, producing dehydrated products with high nutritional content is a feasible and necessary opportunity that would boost industries, promote better nutrition, and reduce waste. S. edule is an alternative with great growth opportunity due to its nutraceutical characteristics, with physiological benefits through seven of the nine essential amino acids. The latter include phenolic compounds that have shown diuretic, anti-inflammatory, and hypotensive effects, providing benefits to both the commercial sector and the producer by developing a product that facilitates consumption and production and takes advantage of the whole vegetable.